2022
DOI: 10.1002/uog.25184
|View full text |Cite
|
Sign up to set email alerts
|

OP08.04: Is it possible to create ultrasonographic Bishop score? Repeatability and reproducibility of potential parameters – preliminary study

Abstract: Objectives: The primary objective was to compare point-of-care ultrasound (POCUS) and routine third trimester ultrasound versus routine antenatal care in reducing the incidence of undiagnosed breech presentation in labour. Methods: We included data from St. George's (SGH) and Norfolk and Norwich University Hospitals (NNUH). Pregnancies were grouped according to whether they received routine third trimester scan (SGH) or POCUS (NNUH). Women with multiple pregnancy, preterm birth < 37 weeks, congenital abnormali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…We estimated the minimal sample size based on the table presented by Bujang et al [ 26 ]. Based on the available literature and the preliminary study, we concluded that the value of the intraclass correlation coefficient (ICC) for the null hypothesis should not be less than 0.5 [ 20 , 24 , 27 ]. With such a null hypothesis, two observations per patient and a power of 90%, the minimum sample size should not be less than 87 subjects.…”
Section: Methodsmentioning
confidence: 99%
“…We estimated the minimal sample size based on the table presented by Bujang et al [ 26 ]. Based on the available literature and the preliminary study, we concluded that the value of the intraclass correlation coefficient (ICC) for the null hypothesis should not be less than 0.5 [ 20 , 24 , 27 ]. With such a null hypothesis, two observations per patient and a power of 90%, the minimum sample size should not be less than 87 subjects.…”
Section: Methodsmentioning
confidence: 99%